Efficacy of bilateral quadratus lumborum block with liposomal bupivacaine for post-cesarean analgesia: a protocol for an open-label randomized controlled trial - Ma, Wenru; Liu, Yinhuan; Li, Yan; Zhu, Kongjuan; Yu, Youjia; Wang, Yanting (Frontiers in Medicine, 2025)
BackgroundEffective postoperative pain management is essential for optimizing maternal comfort and recovery following cesarean delivery. However, achieving adequate analgesia remains a challenge due to suboptimal pain control and medication-related adverse effects. This study aims to evaluate the efficacy of bilateral quadratus lumborum block using liposomal bupivacaine for post-cesarean analgesia.MethodsThis single-center, open-label, randomized controlled trial will enroll 201 adult parturients undergoing lower segment transverse cesarean section. Participants will be randomized in a 1:1:1 ratio into three groups (n = 67 each): Group LB will receive bilateral quadratus lumborum block with liposomal bupivacaine under ultrasound guidance. Group R-P will receive bilateral quadratus lumborum block with ropivacaine in combination with patient-controlled intravenous analgesia. Group P will receive standard patient-controlled intravenous analgesia without regional nerve block. The primary outcome is postoperative pain intensity, assessed using the Visual Analogue Scale during standardized movement at 12, 24, 48, and 72 h postoperatively. A generalized estimating equation model will be used to assess the overall effect of treatment group on pain scores over time. Secondary outcomes include patient-reported Quality of Recovery-15 scores at 24 and 48 h postoperatively; Visual Analogue Scale for pain at rest, measured at 12, 24, 48, and 72 h postoperatively; need for rescue analgesia; postoperative anxiety (assessed by Visual Analogue Scale at 72 h); subjective sleep quality; maximum walking duration; patient satisfaction with analgesia; incidence of nausea and vomiting; postoperative sufentanil consumption and length of hospital stay. Safety outcomes include allergic reactions, wound infection, lightheadedness, headache, circumoral numbness, tongue paresthesia, drowsiness, irritability, blood pressure fluctuations (hypotension, hypertension), respiratory depression (hypoventilation), and cardiac events (bradycardia, tachycardia, arrhythmia, cardiac arrest). Data will be analyzed using a modified intention-to-treat approach.DiscussionThis study aims to provide high-quality evidence on the efficacy of bilateral single-injection quadratus lumborum block with liposomal bupivacaine, compared with standard intravenous analgesia alone and combined with quadratus lumborum block using ropivacaine.Ethics and disseminationEthics approval was obtained from the Ethics Committee of the Affiliated Hospital of Qingdao University (QYFYEC2024-297). All parturients will provide written informed consent. The results of this study will be published in a peer-reviewed journal.Clinical trial registrationIdentifier ChiCTR2500095835.